RENCANA PENINGKATAN STATUS PELABUHAN PERIKANAN NUSANTARA DI PELABUHAN RATU, JAWA BARAT MENJADI PELABUHAN PERIKANAN SAMUDERA - Kevin Adnan Hariel (2022)
Indonesia, is a maritime country, that has a large marine area, with geograpichal conditions in such a way that the potential of Indonesia's natural resources in the marine sector is one of them in the fisheries sector, in utilizing the potential of these natural resources, infrastructure need that supports community activities, especially those who work as fishermen, for example the fishery Port. Fishery Port is a place government activities and fishery business system activities that are used as a place for fishing vessels to dock, dock, and/or unload fish equipped with shipping safety facilities and fishery support activities. Pelabuhan Ratu Nusantara Fisheries Port is located in Pelabuhan Ratu Bay which is part of the Indian Ocean waters (WPP-RI 573). Against the background of the potential for fisheries around Pelabuhan Ratu, the Nusantara Fishery Port (PPN) was built on February 18, 1993 which was inaugurated by the President of the Republic Indonesia. The increase in the PPN status of Pelabuhan Ratu in based several conditions. PPN Pelabuhan Ratu is geograpically located in Pelabuhan Ratu Bay, Sukabumi Regency West Java which is a bay facing directly to the Indian Ocean with topographic contours of up to minus 200 meters deep at a distance of 300 meters from the sheoreline and a depth of minus 600 meters in the center of the bay. The potential at the fisheries sector is very high, but the effectiveness of the loading and unloading donk only reaches 6.42%, and the untilization rate of the loading and unloading dock reaches 423.7%, which means that the Port of Pelabuhan Ratu is overload. So, there needs to be increased status to become an Ocean Fishing Port (PPS). Keywords: Fishery Port, Status Upgrade, PPN Pelabuhan Ratu